2023
DOI: 10.1111/mec.17046
|View full text |Cite
|
Sign up to set email alerts
|

Maternal effect senescence via reduced DNA repair ability in the three‐spined stickleback

Abstract: In many species of animals and plants, survival rate and fertility decrease with advancing age due to senescence. Evolutionary theory explains senescence as a result of age-related declines in the strength of natural selection (Hamilton, 1966), which allow the accumulation of mutations deleterious to late-life performances (Medawar, 1952) and even promote active selection of alleles with deleterious effects in late life but beneficial pleiotropic effects in early life (Williams, 1957). It is well known that ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…The 3-spined stickleback has proven to be an excellent model for investigating the plasticity of the traits directly involved in cognitive processes ( Bell and Foster 1994 ; Brydges et al 2008 ; Feng et al 2015 ). In a parallel experiment, using the same F1 families obtained from the 1-yr-old young females and 2-yr-old senescent females, we demonstrated the presence of maternal effect senescence and showed that the offspring of old mothers had higher rates of malformation and early mortality and had smaller body size at maturity than those of young mothers ( Kim et al 2023 ). In the present experiment, using the offspring obtained from the parallel study, we experimentally tested whether the interplay between maternal age and environmental enrichment experienced during early life affects inhibitory control and learning rate (in a repeated detour-reaching task), brain morphology, growth, survival, and group behavior (i.e.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…The 3-spined stickleback has proven to be an excellent model for investigating the plasticity of the traits directly involved in cognitive processes ( Bell and Foster 1994 ; Brydges et al 2008 ; Feng et al 2015 ). In a parallel experiment, using the same F1 families obtained from the 1-yr-old young females and 2-yr-old senescent females, we demonstrated the presence of maternal effect senescence and showed that the offspring of old mothers had higher rates of malformation and early mortality and had smaller body size at maturity than those of young mothers ( Kim et al 2023 ). In the present experiment, using the offspring obtained from the parallel study, we experimentally tested whether the interplay between maternal age and environmental enrichment experienced during early life affects inhibitory control and learning rate (in a repeated detour-reaching task), brain morphology, growth, survival, and group behavior (i.e.…”
Section: Introductionmentioning
confidence: 65%
“…Thus, the natural lifespan of this population is less than 18 mo in their native habitat. However, under captive conditions in our laboratory, many fish survive and reproduce until the second breeding season because there is no extrinsic mortality by predation, parasitism, extreme weather, and food limitation ( Kim et al 2023 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The significant effect of temperature on mtDNA content at 34 °C adds to the diversity of biological impacts that occur in aquatic communities exposed to thermal stress. To our knowledge, only one previous study has examined the effect of temperature on mtDNA content in teleosts, in which there was an increase in mtDNA content in eggs at warmer winter temperatures (+ 5 °C) in stickleback ( Gasterosteus aculeatus ) 97 . Similarly, an increase in mtDNA content was reported in prawns ( Palaemon carinicauda ) raised in warm water 98 .…”
Section: Discussionmentioning
confidence: 99%